Customization of Conductive Elastomer Based on PVA/PEI for Stretchable Sensors - Wang, Chan; Hu, Kuan; Zhao, Chaochao; Zou, Yang; Liu, Ying; Qu, Xuecheng; Jiang, Dongjie; Li, Zhe; Zhang, Ming‐Rong; Li, Zhou (Small (Weinheim an der Bergstrasse, Germany), 2020)
Conductive, stretchable, environmentally‐friendly, and strain‐sensitive elastomers are attracting immense research interest because of their potential applications in various areas, such as human–machine interfaces, healthcare monitoring, and soft robots. Herein, a binary networked elastomer is reported based on a composite hydrogel of polyvinyl alcohol (PVA) and polyethyleneimine (PEI), which is demonstrated to be ultrastretchable, mechanically robust, biosafe, and antibacterial. The mechanical stretchability and toughness of the hydrogels are optimized by tuning the constituent ratio and water content. The optimal hydrogel (PVA2PEI1‐75) displays an impressive tensile strain as high as 500% with a corresponding tensile stress of 0.6 MPa. Furthermore, the hydrogel elastomer is utilized to fabricate piezoresistive sensors. The as‐made strain sensor displays seductive capability to monitor and distinguish multifarious human motions with high accuracy and sensitivity, like facial expressions and vocal signals. Therefore, the elastomer reported in this study holds great potential for sensing applications in the era of the Internet of Things (IoTs). A binary networked elastomer based on polyvinyl alcohol (PVA) and polyethyleneimine (PEI) exhibits ultrastretchable, mechanically robust, biosafety, and antibacterial properties. Through optimizing the constituent ratio and water content, the composite hydrogel displays seductive elasticity and is further used to monitor and distinguish multifarious human motions with high accuracy and sensitivity, like facial expressions and vocal signals.